High rates of unprotected anal intercourse with regular and casual partners and associated risk factors in a sample of ethnic Malay men who have sex with men (MSM) in Penang, Malaysia. Issue 8 (20th June 2013) - Lim, Sin How; Bazazi, Alexander Reza; Sim, Clarence; Choo, Martin; Altice, Frederick L; Kamarulzaman, Adeeba
Abstract : Objective: To assess the prevalence of unprotected anal intercourse (UAI) and its correlates among ethnic Malay men who have sex with men (MSM). Methods: In 2010, a convenience sample of 350 MSM in Penang were recruited to participate in an anonymous, computerised survey with rapid HIV testing. Participants who were not of Malay ethnicity (n=44) or who did not report sex with another man in the previous 12 months (n=22) were excluded, resulting in 284 participants in the final analysis. Correlates of UAI were examined separately for regular and casual partnerships using bivariate and multivariate logistic regression. Results: Four men (1.9%) tested HIV positive. In the past 12 months, 64.7% of participants had regular sexual partners, 77.1% had casual sexual partners and 41.9% had both. Most participants (83.1%) reported UAI, which was more common in regular partnerships. Over two-thirds of participants had never been tested for HIV. In multivariate analysis, agreement about sexual risk reduction practices was associated with a reduction in UAI with regular partners (adjusted OR (AOR)=0.14, 95% CI 0.05 to 0.40). Reporting difficulty in using condoms was associated with an increase in UAI with casual partners (AOR=9.07, 95% CI 3.35 to 24.5), and any exposure to HIV prevention was associated with a decrease in UAI with casual partners (AOR=0.22, 95% CI 0.09 to 0.54). Conclusions: Despite highly prevalent HIV risk behaviours, HIV seropositivity and prior HIV testing were low. Increasing sexual negotiation skills and access to HIV testing and other prevention services may improve future prevention efforts.